2016
DOI: 10.12989/sss.2016.17.3.391
|View full text |Cite
|
Sign up to set email alerts
|

Mode identifiability of a multi-span cable-stayed bridge utilizing stabilization diagram and singular values

Abstract: This study investigates the mode identifiability of a multi-span cable-stayed bridge in terms of a benchmark study using stabilization diagrams of a system model identified using stochastic subspace identification (SSI). Cumulative contribution ratios (CCRs) estimated from singular values of system models under different wind conditions were also considered. Observations revealed that wind speed might influence the mode identifiability of a specific mode of a cable-stayed bridge. Moreover the cumulative contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Only the first six modes are considered in this research, and the identification results are listed in Table 8. For better comparing the identification results, the modal parameters identified in similar studies 55,56 are also listed in Table 8 (second column). It can be found that the modal parameters identified via the two methods are close to those results, but there is some deviation for uncertainty quantification, even in the c.o.v.s of the frequencies (see SSI f 2 , as well as Bayesian f 1 , f 3 , and f 6 ).…”
Section: Comparison Of Tkb Identification Results From Ssi and Bayesian Methodsmentioning
confidence: 99%
“…Only the first six modes are considered in this research, and the identification results are listed in Table 8. For better comparing the identification results, the modal parameters identified in similar studies 55,56 are also listed in Table 8 (second column). It can be found that the modal parameters identified via the two methods are close to those results, but there is some deviation for uncertainty quantification, even in the c.o.v.s of the frequencies (see SSI f 2 , as well as Bayesian f 1 , f 3 , and f 6 ).…”
Section: Comparison Of Tkb Identification Results From Ssi and Bayesian Methodsmentioning
confidence: 99%
“…During the impact test, 13 sensors were installed on the pier and connected girders to distinguish the pier-oriented mode with the girder modes. Stochastic subspace identification (SSI) [4] was utilized to identify modal parameters for the impact test, and the stabilization diagram (SD) [5] was used to decide steady vibration modes. Fig.…”
Section: Reference Natural Frequency Of the Target Piermentioning
confidence: 99%
“…Conventional methods, also known as direct methods , involve numerous sensors installed along the bridge to monitor the vibration response excited by traversing vehicles or other excitations. Over the past decades, scholars have carried out a large amount of research on these direct methods [ 6 , 7 , 8 , 9 ]. The limitation of the direct methods lies in the high cost of equipment installation and maintenance, together with the manual labor consumption and the interruption of the traffic flow [ 10 ].…”
Section: Introductionmentioning
confidence: 99%